Performance appraisal politics and employee turnover intention - Ahmad, Rusli; Lemba, Camclia; Wan Ismail, Wan Khairuzzaman (Fakulti Pengurusan UTM, 2010)
This study examines the effect of performance appraisal politics on employee turnover intention. Past research shows that there is evidence that ratings of performance appraisal had often been manipulated for political purposes and motives. This research focuses on two elements or political motives influencing employee turnover intention: motivational and punishment motive. The study used survey research to gather 60 questionnaires from a private company. The findings show that there is a positive relationship between the independent variables (motivational motive and punishment motive) with dependent variable (employee turnover intention). Results of multiple regression analysis show that punishment motive have more effects towards employee turnover intention compared to motivational motive. The implications and recommendations of the study also were also discussed.